Mile Marker : A Material Investigation in Two Lane Travels - James, Danielle (East Carolina University, 2014)
This thesis contemplates American imagery, landscape, memories, identities, and travel in order to introduce the spontaneity of adventure to the viewer. My work attempts to spark a desire for being lost and focuses on the memorialization of the journey instead of a destination. Embedding my narratives into wearable objects enables an exchange of personal experience between the wearer and myself in order to share and collect personal insights about our world.  The formulation of this work relies on photographic documentation, information from historical preservation societies, and community interaction to preserve certain aspects of a location I observe. I record the distinctive economic, architectural and social curiosities of a site with photography and sketches that are later distilled into wearable jewelry.  In these recollections of regionalism I imitate and miniaturize materials like bricks, I-beams, roofing and road signs using jewelry and metalsmithing materials. I memorialize a location and create a narrative as a reminder to the wearer of the decline of the two lane blacktops that connect this country.
Keywords: Fine arts; America; Metalsmithing; Regionalism; Road trip; Storytelling; Jewelry making; Metal-work; Roads in art